Assessment of Microbial Quality of Chlorinated Drinking Tap Water and Susceptibility of Gram-Negative Bacterial Isolates towards Chlorine - Bishankha, S.; Bhatta, D. R.; Joshi, D. R.; Joshi, T.P. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Sixty (56.1%) water samples crossed the permissible limit of WHO guideline value in heterotrophic plate count and total coliform count each. Ten different genera of gram-negative bacteria were recovered, among which E. coli was predominant followed by Citrobacter spp., Shigella spp., Enterobacter spp., Providencia spp., Klebsiella spp., Salmonella spp., Pseudomonas spp., Proteus spp., and Edwardsiella spp. Higher the temperature of water sample, higher the bacterial growth was obtained (p= 0.002), and similarly, a higher level of free residual chlorine in water reduced the bacterial growth (p= 0.037). However, increase or decrease of pH (p= 0.454), turbidity (p= 0.164), and conductivity (p= 0.969) didn’t affect the microbial growth. A negative correlation (r= -0.162) between heterotrophic plate count and free residual chlorine was observed, but without statistical significance (p= 0.096). Similarly, a negative correlation (r= -0.383) between total coliform count and free residual chlorine was observed with statistical significance (p= 0.001). In the chlorine assay, all tested eight different genera of gram-negative bacteria were found to be chlorine resistant at 0.2 mg/L for a contact time of 30 minutes. The average time required for T99.9 (3-log) and T99.99 (4-log) reduction of viable isolates from the initial population of 2×106 cells/mL were found to be less than 30 minutes and greater than 60 minutes respectively. Log inactivation of various bacterial isolates with a chlorine concentration of 0.2 mg/L for a contact time of 30 minutes ranged from 3 to 3.5-log. The emergence of chlorine-resistant organisms in drinking water probably demands alternate disinfection or mitigation strategy.